AI and cybersecurity: a risk society perspective - Vulpe, Simona-Nicoleta; Rughiniș, Răzvan; Țurcanu, Dinu; Rosner, Daniel (Frontiers in Computer Science, 2024)
IntroductionThe rapid evolution of Artificial Intelligence (AI) has introduced transformative potential across various sectors, while simultaneously posing significant cybersecurity risks.MethodsThe aim of this paper is to examine the debates on AI-related cybersecurity risks through the lens of Beck’s theory of the risk society. Utilizing thematic content analysis, we explored public discourse on AI and cybersecurity as presented in articles published by WIRED.ResultsOur analysis identified several key themes: the global nature of AI risks, their pervasive influence across multiple sectors, the alteration of public trust, the individualization of risk, and the uneven distribution of AI risks and benefits.DiscussionThe editorial choices in WIRED predominantly favor a functionalist and solutionist perspective on AI cybersecurity risks, often marginalizing the opinions of ordinary individuals and non-Western voices. This editorial bias tends to limit diversity and underrepresent key opposing viewpoints, potentially hindering a more comprehensive and nuanced debate on AI and cybersecurity issues.